Determination of radon concentration in groundwater of Gadau, Bauchi State, Nigeria and estimation of effective dose - Shu'aibu, H. K.; Khandaker, Mayeen Uddin *; Baballe, A.; Tata, S.; Adamu, M. A. (Elsevier, 2021)
Owing to its proximity to rock and soil, groundwater may contain a non-negligible amount of naturally occurring radioactive materials. If so, the drinking water sourced from deep-bore wells may pose great harm to human health. Acknowledging that water plays a vital role in maintaining a healthy lifestyle, it is important to study the radiological implications of radon gas associated with the intake of groundwater. A total of 10 groundwater samples were analyzed using RAD7 alpha spectrometry (Durridge Co., USA). The measured radon concentration was found to be in the range of 4.92–82.89 (mean 38.3 Bq l−1), which is higher than the US-EPA reference level of 11.1 Bq l−1 or 300 pCi l−1 but within the permissible limit of 100 Bq/m3 set by WHO and EU for indoor radon level (i.e., for inhalation pathway). The values obtained from the studied media were found to be relatively higher than most of the data available in the literature. The mean annual effective dose for ingestion (8.05 μSv y−1) and inhalation (0.10 μSv y−1) was found to be significantly lower than the action level recommended by WHO (0.1 mSv y−1) and ICRP (3–10 mSv y−1), due to 222Rn, 3H and 40K in drinking water. Note that, such a comparison may not reflect the real scenario since our estimated dose is only contributed to by 222Rn. However, the obtained data could serve as a reference for any future radiological study of the waterbody in this region.